Analisis Sistematis tentang Bagaimana Analisis Big Data Mempengaruhi Pengambilan Keputusan Bisnis dalam Sistem Informasi Manajemen - Muhammad Iffan; Muhamad Nur Ramadhan; Arjuna Rizaldi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2026)
This study examines how can Big Data Analytics contributes to better business decision-making through the use of Management Information Systems. This research is driven by the urgent need for organizations to make faster and more accurate decisions amidst intense competition as traditional information systems are no longer able to handle large and complex data. This study adopted a literature observation method compiled with PRISMA guidelines which analyzed a total of 20 scientific articles to investigate the latest research that discusses the relationship between analytical capabilities and systems in supporting management processes. The results show that the collaboration between Big Data Analytics and MIS can help companies understand market changes, assess operational efficiency, and formulate strategies based on real-time information. However, issues related to data accuracy, system readiness, and a shortage of skilled personnel remain major obstacles in this research. This study is recommended to understand how the use of analytics in Management Information Systems (MIS) can improve decision-making quality and organizational performance, while emphasizing the importance of balancing technology, human capabilities, and managerial practices. Keywords: Big Data Analytics; Management Information Systems; Decision Making; Business Intelligence; Systematic Literature Review